Colletotrichum acutatum associated with Dryocosmus kuriphilus galls on Castanea sativa. Issue 2 (6th March 2015) - Gaffuri, F.; Maresi, G.; Pedrazzoli, F.; Longa, C. M. O.; Boriani, M.; Molinari, M.; Tantardini, A.; Sieber, T.
Summary The occurrence of Colletotrichum acutatum J. H. Simmonds in necrotized galls of Dryocosmus kuriphilus Yasumatsu in chestnut (Castanea sativa Miller) stands is reported for the first time in Italy. Morphological and biomolecular analyses confirmed the isolation of the fungus. No damage by the fungus has been observed.